Diversity and biosynthetic potential of fungi isolated from St. John's Island, Singapore - Munusamy, Madhaiyan (2023)
Adaptation to a wide variety of habitats allows fungi to develop unique abilities to produce diverse secondary metabolites with diverse bioactivities. In this study, 30 Ascomycetes fungi isolated from St. John's Island, Singapore were investigated for their general biosynthetic potential and their ability to produce antimicrobial secondary metabolites (SMs). All the 30 fungal isolates belong to the Phylum Ascomycota and are distributed into 6 orders and 18 genera with Order Hypocreales having the highest number of representative (37%). Screening for polyketide synthase (PKS) and nonribosomal peptide synthetase (NRPS) genes using degenerate PCR led to the identification of 23 polyketide synthases (PKSs) and 5 nonribosomal peptide synthetases (NRPSs) grouped into nine distinct clades based on their reduction capabilities. Some of the identified PKSs genes share high similarities between species and known reference genes, suggesting the possibility of conserved biosynthesis of closely related compounds from different fungi. Fungal extracts were tested for their antimicrobial activity against S. aureus, Methicillin-resistant S. aureus (MRSA), and Candida albicans. Bioassay-guided fractionation of the active constituents from two promising isolates resulted in the isolation of seven compounds: Penilumamides A, D, and E from strain F4335 and xanthomegnin, viomellein, pretrichodermamide C and vioxanthin from strain F7180. Vioxanthin exhibited the best antibacterial activity with IC50 values of 3.0 μM and 1.6 μM against S. aureus and MRSA respectively. Viomellein revealed weak antiproliferative activity against A549 cells with an IC50 of 42 μM. The results from this study give valuable insights into the diversity and biosynthetic potential of fungi from this unique habitat and forms a background for an in-depth analysis of the biosynthetic capability of selected strains of interest with the aim of discovering novel fungal natural products.